Crying Wolf: An Analysis of the Use of Sensational Content within the Media and the Desensitizing Effects it has on Audiences - Lowe, Lindsey (2016)
This thesis examines the development and use of sensational media content to analyze this growing phenomenon and the effects that it has had on audiences. This research focuses primarily on specific examples of sensational media content including: The Arrival of a Train at La Ciotat, The Great Train Robbery, the “War of the Worlds” broadcast, the Hindenburg disaster, footage of the Vietnam War, Apollo 11 and the first moon landing, and The Day After. These examples were chosen to chronicle the development and use of sensationalism and to illustrate that media audiences of today are desensitized to sensational content because the vicarious, successional use of this ultra-real content has progressively led audiences to believe sensational content is the norm within media. The historical analysis approach was chosen for this particular research because sensationalism is a phenomenon that has developed over a long period of time, and this approach allows for the researcher to encompass the origins, growth, and trends of this phenomenon when making conclusions about the collective research. This research suggests that the progressional exposure to sensational content has desensitized audiences and raised the baseline for what is considered sensational in media today